Breathing lessons : a doctor's guide to lung health - Han, MeiLan K. (W.W. Norton & Company, 2022)
"An authoritative, accessible guide to how our lungs work and how to protect them. Most of us pay little attention to the workings of our lungs, but the COVID-19 pandemic has sparked interest in their functioning and fear about the risks they face. Dr. MeiLan K. Han, a leading pulmonologist and a national spokesperson for the American Lung Association, takes readers on a fascinating tour of this most vital organ. Han explains the wonder of breathing and reveals how the lungs serve as the body's first line of defense. She provides a timely overview of the latest scientific thinking about the leading respiratory risks-including indoor and outdoor pollution, smoking and vaping, wildfire smoke, and viruses like SARS-CoV-2-and offers a practical guide to keeping lungs healthy. And with authority as both practitioner and medical researcher, she argues powerfully for a social policy that makes a priority of preserving lung health nationwide"--